Improvement of methods of diagnosis and treatment of patients with obstructive jaundice of tumor genesis - E. B. Revazov; T. S. Khutiev; M. R. Revazova; A. N. Chetiev; U. S. Beslekoev; T. B. Ardasenov (Вестник хирургии имени И.И. Грекова)
The Objective was to improve medical and diagnostic care for patients with obstructive jaundice of tumor genesis.Methods and Materials. Retrospective analysis of the treatment results of 309 patients with obstructive jaundice of tumor genesis. We studied the results of endoscopic transpapillary and/or percutaneous transhepatic antegrade endobilliary minimally invasive surgical interventions of 307 (99.3 %) patients. We carried out the analysis of complications, reasons and possible elimination path. A new, more effective method of trepan-biopsy of tumors of the pancreatic head and distal choledochus and devise for it implementation were developed (patent № 2722655, 2747591).Results. Minimally invasive decompression interventions at the first stage of treatment of patients with obstructive jaundice of tumor genesis reduced the percentage of fatal postoperative complications to 1.3 %. The first results of the application of the developed trepan-biopsy method showed their high efficiency, reliability and safety.Conclusion. The differentiated approach to the choice of the method of decompression of the biliary tract at the first stage is important for improving the results of treatment. The use of the method of simultaneous puncture transhepatic billioduadenal drainage with trepan-biopsy of tumors of the pancreatic head and distal choledochus is, as it seems to us, a new, promising adjustment in solving the problem of morphological verification of tumors of the hepatopancreatoduodenal zone and reducing the time of diagnosis and treatment of patients with obstructive jaundice of the tumor genesis.